A GESTÃO EDUCATIVO-CULTURAL PARA A TERCEIRA IDADE. A EXPERIÊNCIA DO SESC PAULISTA - Chasles, Marco Antonio (2009)
It is clear to see the elderly s more active life as well as an increase on the demand for centers that can offer leisure, culture, interaction and learning possibilities on the part of this group. Seeing that, the purpose of this work is to study SESC s department for the third age, named GETI (Gerência de Estudos e Programas para Terceira Idade). It will attempt to delineate a clearly defined historical line that approaches its creation, structure, form, management and main actions performed with the elder. Also understanding SESC as a possible third sector activity profile. In order to verify the effectiveness of the actions taken, this work investigates the modus operandi of three SESC units which currently provide the so-called TSI (Trabalho Social com o Idoso) by understanding how coordinators in each unit elaborates those actions and the results of this work through the elderly s eyes user. The research and gathering information has been conducted by means of secondary data from bibliographical and documental survey in public sources, like SESC itself, besides the recent research about elderly carried out by Fundação Perseu Abramo. This way, the program, its methodology, guidelines and peculiarities were analyzed. The work was done under a descriptive qualitative survey that brought forth the administration s important elderly cultural-educational aspects, besides an in-depth survey with GETIS s managers, coordinators and the invaluable contribution of SESC s gerontologists and collaborators. To make possible the analysis of whether there had been divergence in the understanding of such actions or not, the author tried to identify this matter through an oral narrative with the elderly. This way, was possible to understand the subject-matter from SESC s management to its users.(AU)